Can Quantum Contextuality Help to Understand the Contextuality of Theology? - Grygiel, Wojciech P. (Theology and science, 2024)
The precise formal account of the contextuality of the quantum measurement provided by the Kochen-Specker theorem allows for a unique insight into the nature of the contextuality of theological language. The conceptual analysis carried out in this paper has demonstrated that despite of the methodological difficulties in juxtaposing theoretical physics and theology, legitimate bridges can be established between them whereby quantum contextuality may serve as a model of contextuality in theology. A structural factor in the form of a richer logic proper to the Divine nature has been identified as the possible source of contextuality of theological discourse.